2009
DOI: 10.1128/jvi.01175-09
|View full text |Cite
|
Sign up to set email alerts
|

NKG2D Ligand MICA Is Retained in thecis-Golgi Apparatus by Human Cytomegalovirus Protein UL142

Abstract: Human cytomegalovirus (HCMV) evades T-cell recognition by down-regulating expression of major histocompatibility complex (MHC) class I and II molecules on the surfaces of infected cells. Contrary to the "missing-self" hypothesis, HCMV-infected cells are refractory to lysis by natural killer (NK) cells. Inhibition of NK cell function is mediated by a number of HCMV immune evasion molecules, which operate by delivering inhibitory signals to NK cells and preventing engagement of activating ligands. One such molec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
97
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 101 publications
(99 citation statements)
references
References 62 publications
2
97
0
Order By: Relevance
“…The Gateway compatible pCMV-Myc vector was kindly provided by Dr. K. Helin (Biotech Research and Innovation Centre, University of Copenhagen) (30). The GFP-MICA*018 plasmid that contained the fulllength allele MICA*018 downstream of a generic leader, a GFP cassette, and a myc tag was kindly provided by Dr. M. Wills (University of Cambridge, Cambridge, U.K.) (31).…”
Section: Transient Transfectionsmentioning
confidence: 99%
“…The Gateway compatible pCMV-Myc vector was kindly provided by Dr. K. Helin (Biotech Research and Innovation Centre, University of Copenhagen) (30). The GFP-MICA*018 plasmid that contained the fulllength allele MICA*018 downstream of a generic leader, a GFP cassette, and a myc tag was kindly provided by Dr. M. Wills (University of Cambridge, Cambridge, U.K.) (31).…”
Section: Transient Transfectionsmentioning
confidence: 99%
“…N-terminal GFP-tagged UL142 was constructed as described previously (38). All plasmids were prepared using a Nucleobond Maxi Xtra method (Machery Nagel, DĂźren, Germany) and resuspended in Tris-EDTA or water.…”
Section: Vector Constructsmentioning
confidence: 99%
“…In addition, we previously showed that UL142 localizes to the ER and cis-Golgi (37,38) and that transduction of UL142 is sufficient to protect cells from NK cell-mediated lysis, whereas reducing UL142 translation with RNA interference during HCMV infection increases NK cellmediated cytotoxicity (37). UL142 can also downregulate the products of full-length alleles of MICA by intracellular retention in the Golgi complex (33,38). Although these effects of UL142 have been proposed as the mechanism by which it exerts protection against NK cells, surface levels of truncated MICA protein (encoded by the p 008 allele) were not downregulated.…”
mentioning
confidence: 97%
See 1 more Smart Citation
“…Compared with the genome of the prototype laboratory strain, AD169, genomes of low-passage HCMV clinical isolates contain the UL/b' region, including ORFs UL133-UL151, considered as a critical candidate cluster to clinical pathogenesis (3). Although the UL/b' region is not essential to viral growth or replication (4), products of this region, including UL141, UL142 and UL144 have been experimentally identified to aid in viral escape from immune surveillance through interactions with cellular molecules (5)(6)(7)(8)(9)(10).…”
Section: Introductionmentioning
confidence: 99%